Super-Thin and Suprafascial Anterolateral Thigh Perforator Flaps for Extremity Reconstruction - Seth, Akhil K.; Iorio, Matthew L. (Journal of Reconstructive Microsurgery, 2017)
Background The anterolateral thigh (ALT) flap remains a workhorse for soft tissue reconstruction. However, the traditional ALT flap is often too bulky for resurfacing shallow, distal extremity defects, prohibiting adequate function, or well-fitted orthotics. This study evaluates extremity reconstruction using ALT flaps elevated in the suprafascial or super-thin plane.Methods Retrospective review of ALT free flap reconstruction from October 2014 to July 2016 was performed. Suprafascial and super-thin flaps were those elevated just above the crural fascia and within the superficial scarpal plane, respectively. Adjunct operative procedures, demographics, and complications were recorded.Results A total of 25 patients underwent suprafascial (n = 14) or super-thin (n = 11) ALT flap reconstruction for primarily lower extremity wounds (n = 19), with an average age and body mass index of 53.8 years and 26.3 kg/m2, respectively. Follow-up was 6.3 months. Comorbidities included smoking (n = 7), diabetes (n = 8), peripheral vascular disease (n = 6), and hypertension (n = 8). The presence of hardware (n = 9), trauma (n = 10), and chronic infection (n = 12) were common risk factors. Average flap size was 8.2 × 21.5 cm, with 64% (n = 16) taken on one perforator. Forty-eight percent (n = 12) were end-to-side anastomoses and 62% (n = 13) utilized one venous anastomosis. Mean hospital stay was 7.8 days with a 24% (n = 6) complication rate. There were no partial or complete flap losses.Conclusion The ALT flap, elevated in a suprafascial or super-thin plane, is a safe, effective option for extremity soft tissue reconstruction. The decreased flap volume and bulk provides the improved contour and pliability necessary for appropriate distal extremity function. The potential versatility of super-thin flaps reinforces the importance of continued innovation by reconstructive microsurgeons.
Keywords: anterolateral thigh flap; extremity reconstruction; free flap